Alternatives For Providing Compensation For The Detention Of A Defendant Whose Case Is Acquitted - Akbar, Aristian (Pancasila and Law Review, 2022)
The pretrial process creates uncertainty in compensating defendants who are acquitted and have final legal status. This research examines alternatives to pretrial compensation by analyzing criminal law policies. Using normative and sociological juridical approaches, and relying on secondary and primary data from library research and interviews, the research identifies two main alternatives: (1) including compensation within the court decision for damages caused by the criminal act, and (2) providing compensation through Alternative Dispute Resolution (ADR) with court approval. The legal implication is that the state must fulfill its obligation to pay compensation if granted; otherwise, a denial could negatively affect the defendant’s social, economic, and human rights.